Research on heliostat field design based on mesh search optimization algorithm - Luo, Lei (Transactions on Computer Science and Intelligent Systems Research, 2024)
Nowadays, heliostat field has been gradually put into practical production, how to design heliostat field to make the highest efficiency of light energy utilization is an important problem. By establishing the adjustment model of heliostat, the design problem of heliostat field is studied by using the mesh search optimization algorithm. First, the position of the absorption tower is determined, so that the heliostat is closely arranged, and then the annual average output thermal power per unit mirror area is as large as possible as the objective function. The optimization model is established for the size requirements, installation height and center distance of the heliostat as the constraint conditions, and then the grid search algorithm is used to solve the problem and remove the heliostat with low output thermal power. Until the selected 60MW rated average annual thermal output power is reached, the result is that the average annual thermal output power per unit area of the mirror is 0.6011kw/m2 under the same heliostat size and the average annual thermal output power per unit area of the mirror is 0.6138kw/m2 under different heliostat sizes. The feasibility and accuracy of the model are verified by a concrete example, which lays a foundation for the design of defining the mirror field.